(untitled) (Third Sector Social Economic Review, 2025)
Digitalization has ushered in an era of new technologies that have transformed the traditional way of working and led to the emergence of non-standard forms of employment. Labor has shifted from the real world to the virtual digital world and digital labor has become an important part of the form of labor in modern society. This article aims to reflect the development of international literature on digital labor by conducting a bibliometric analysis of publications indexed in the Web of Science database. In the research, 577 documents obtained from the database were analyzed using VOSviewer software. The results of this study show that digital labor is most intensively studied under the perspectives of communication, sociology and industrial relations. The most prolific author between 2004 and 2024 is Christian Fuchs with 19 articles. The results show that the most frequently used keywords in studies since 2004 are digital labor, gig economy and social media. The most recent keywords used in digital labor studies are algorithmic management, algorithms, digital economy and platforms. It is thought that the results of this study will provide a roadmap for future research directions.